Application of Fuzzy Logic Through Bellmen-Zadeh Maximin Method - Paudel, Gyan Prasad; Pahari, Narayan Prasad; Kumar, Sanjeev (Journal of Nepal Mathematical Society, 2022)
Fuzzy Logic is a multiple valued logic, from which the truth values of variables might be any real numbers between 0 and 1. It has wide application in different fields of real life. We might face different challenges in our daily life to select the best of the best for the concrete result. There are various criteria in the literature for ranking alternatives in the realm of decision-making under uncertainty in a crisp environment. In this paper, we address the challenges seen in making a decision for selecting the best of the best as studied by Bellmen-Zadeh maximin method. It is used to address such challenges using fuzzy real numbers.